What Do Adult Graduate Students Want? Using the Typology of Cognitive/Affective/Psychomotor Learning Domains to Explore Good and Bad Learning Experiences - Marianne Reiff; Amy Ballin (Adult Education Research Conference, 2008)
Adult graduate students in five cohorts nation-wide listed factors of good and bad learning experiences; factors were sorted into cognitive, affective, and psychomotor categories. Overall a high frequency of response in the affective domain was revealed. Instructor/student relationship was prominent. This work can inform curricular and faculty development design decisions.
Keywords: adult learning environments; cognitive; affective; psychomotor domains